1518 Comparing disability and return to work outcomes between alternative and traditional workers' compensation programs. (24th April 2018) - Ryan, A; Schofield, K
Abstract : Introduction: In 1995, Minnesota, United States, passed legislation to allow for an alternative workers' compensation system and the Union Construction Workers' Compensation Program (UCWCP) was developed. Its goals include the use of pre-approved medical and rehabilitation providers, dispute resolution, and prioritising a quick and safe return to work. The aim of this study is to determine if differences in recovery-related outcomes exist between UCWCP and traditional workers' compensation programs (TWCP). Methods: Workers' compensation claim data for the period 2003–2016 were obtained from the Minnesota Department of Labour and Industry. Claims were classified as processed through UCWCP or TWCP. Outcomes for this study included: permanent partial disability (PPD) and Temporary Total Disability (TTD). The relative risk (RR) of incurring PPD and sustained TTD in UCWCP versus TWCP was calculated using log binomial regression. Ordered logistic regression models were utilised to calculate the odds of higher percentages of PPD in UCWCP. All estimates were adjusted for age, gender, and insurance carrier. Results: Of 33 682 claims, 3269 (9.7%) were processed through UCWCP. The mean claim durations for UCWCP and TWCP were 54 and 49 weeks, respectively. While UCWCP claims, versus TWCP, were associated with an increased risk of PPD (RR=1.2, 95% CI: 1.1 to 1.3), they had increased odds of lower percent PPD (Odds Ratio=1.2, 95% CI: 1.1 to 1.4). Sustained TTD was more likely in UCWCP compared to TWCP (RR=2.0, 95% CI: 1.4 to 3.0). Conclusions: While the increased risks of permanent partial and sustained temporary total disability ratings among UCWCP claims may reflect higher severity, the lower percentage of disability could result from improvements in access and quality of healthcare treatments. Further work will identify and control for relevant severity indicators.